The impact of independent fact-checking on journalism practice in South Africa - Van Wyk, Carina (My University, 2021)
With the practice of independent fact-checking growing worldwide and in Africa (Graves & Cherubini, 2016; Funke, 2019; Bell, 2019; Stencel & Luther; 2020b) this research examines its perceived impact on journalism practice in South Africa. The purpose of the study is to establish whether the work done by fact-checking organisations is considered to have an impact on journalism practice (and by extension practices in newsrooms and news coverage) in South Africa and, if so, to what extent. It also explores the relationship between independent fact checking organisations and the media, and how journalists perceive the practice of dedicated1 fact-checking as practised by independent fact-checkers. Through this research I aim to contribute to the fairly limited research in the field of independent fact-checking, especially in South Africa. The study is all the more important as research on the influence of fact-checking on journalists and journalistic discourse is particularly scarce (Graves, Nyhan & Reifler, 2015; Cheruiyot & Ferrer-Conill, 2018:964). In light of the Covid-19 pandemic, which broke out shortly after the research started, and the subsequent spread of misleading and false information related to the disease (Ali, 2020; Van der Linden, Roozenbeek & Compton, 2020; World Health Organization, 2020), establishing the possible impact of independent fact checking on newsrooms and news coverage – and thus on the information consumed by media audiences – is arguably more relevant than ever.
A research report submitted in fulfilment of the requirement for the degree Master of Arts in Journalism and Media Studies to the Faculty of Humanities, School of Human and Community Development, University of the Witwatersrand, 2021